DEVELOPMENT OF TRAVELING EQUIPMENT FOR CONSTRUCTION AND MAINTENANCE OF RAILROAD TRACK BASED ON 14-TON CLASS EXCAVATOR - Kwon, Jiwoon; Lee, Myunggyu (International Journal of Engineering Technologies and Management Research, 2018)
The unique traveling mechanism was established and investigated by a coordinated modeling and experimental effort and both results are compared for validation of newly developed traveling equipment based on the conventional excavator system. The various hydraulic characteristics such as flow rate, pressure, revolutions per minute (RPM), and torque was confirmed by numerical and experimental technique with the appropriate test bench. After the above processes, the experimental and analytical results were successfully correlated. As a result, this new traveling equipment can contribute to save the outstanding monetary cost during railway construction and maintenance in that this equipment facilitates the accessibility of the conventional excavator into the work site composed of the railroad track.